Emerging role of free triiodothyronine in patients with anti-N-methyl-D-aspartate receptor encephalitis - Tuo Ji (Nature Portfolio, 2021)
Abstract We aimed to investigate the role of free triiodothyronine (FT3) in patients with anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis. 137 consecutive inpatients (2016–2019) were registered prospectively and followed up for 12 months. 96 eligible patients were included in the study. The modified Rankin scale (mRS) score was collected, and the score of 3–6 was defined as a poor outcome. The patients were equally classified into 3 subgroups based on their FT3 levels obtained within 24 h of admission, and the subgroup differences were analyzed by parametric or nonparametric tests as appropriate. Logistic regression analysis was performed. We found that there was no difference in the mRS scores upon admission among 3 subgroups, however, patients in the low-FT3 subgroup tended to have higher disease severity during hospitalization and worse outcome in follow-up visits, represented by higher chances of intense care unit (ICU) admission (P < 0.001), longer hospital stay (P < 0.001), greater maximum mRS scores during hospitalization (P = 0.011), lower rates of getting clinical improvement within 4 weeks of starting treatment (P = 0.006), and higher percentages of poor 1-year outcome (P = 0.002). The level of FT3 was an independent factor correlated with ICU admission (P = 0.002) and might be a potential predictor for 1-year outcome. Our preliminary results suggest that the FT3 may be a risk factor involved in the evolution and progression of anti-NMDAR encephalitis, whereas the underline mechanisms remain to be explored. Attention should be paid to these patients with relatively low FT3 upon admission, which might possibly aid clinical prediction and guide clinical decision-making.